Widespread occurrence of the JAK2 V617F mutation in chronic myeloproliferative disorders - Jones, Amy V.; Kreil, Sebastian; Zoi, Katerina; Waghorn, Katherine; Curtis, Claire; Zhang, Lingyan; Score, Joannah; Seear, Rachel; Chase, Andrew J.; Grand, Francis H.; White, Helen; Zoi, Christine; et al. (Blood, 2005)
The analysis of rare chromosomal translocations in myeloproliferative disorders has highlighted the importance of aberrant tyrosine kinase signaling in the pathogenesis of these diseases. Here we have investigated samples from 679 patients and controls for the nonreceptor tyrosine kinase JAK2 V617F mutation. Of the 480 myeloproliferative disorder (MPD) samples, the proportion of positive cases per disease subtype was 30 (20%) of 152 for atypical or unclassified MPD, 2 of 134 (2%) for idiopathic hypereosinophilic syndrome, 58 of 72 (81%) for polycythemia vera, 24 of 59 (41%) essential thrombocythemia (ET), and 15 of 35 (43%) for idiopathic myelofibrosis. V617F was not identified in patients with systemic mastocytosis (n = 28), chronic or acute myeloid leukemia (n = 35), secondary erythrocytosis (n = 4), or healthy controls (n = 160). Homozygosity for V617F was seen in 43% of mutant samples and was closely correlated with chromosome 9p uniparental disomy. Homozygosity was significantly less common in ET compared with other MPD subtypes. In 53 cases analyzed, the median level of PRV1 expression was significantly higher in V617F-positive cases compared with cases without the mutation. We conclude that V617F is widespread in MPDs. Detection of this acquired mutation is likely to have a major impact on the way patients with MPD are diagnosed, as well as serving as an obvious target for signal transduction therapy. (Blood. 2005;106:2162-2168)